Analisis Perbandingan Kepemimpinan Partisipatif dengan Kepemimpinan Direktif dalam Organisasi - Leana Angelina; Maria Merry Marianti; Regina Deti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the comparison between participative and directive leadership in organizations, identifying the advantages, disadvantages, and appropriate situations for their implementation. The research method used is descriptive with a qualitative approach through a literature study, focusing on relevant articles published between 2020 and 2024. The results show that participative leadership increases work motivation, employee satisfaction, and encourages creativity, but may face challenges in making quick decisions and handling disagreements. In contrast, directive leadership is more effective in crisis situations and structured environments, but it may decrease long-term motivation if applied continuously. The conclusion of this study indicates that both leadership styles have their respective advantages and disadvantages, which should be adapted to the situation and team characteristics. Organizations are advised to implement a flexible leadership style based on existing conditions to achieve organizational goals effectively.